Weather Information for Garden City, 2024 - Colt McElroy (Kansas Agricultural Experiment Station Research Reports, 2025)
Summary of 2024 weather for research conducted at the research locations included in the 2025 Western Kansas Agricultural Research report.
Keywords: Weather; precipitation; Garden City; Kansas; temperature; wind; evaporation